UTILIZATION PATTERN OF ANTENATAL CARE IN LUCKNOW UNDER NATIONAL RURAL HEALTH MISSION - Sharma, Vasundhara; Mohan, Uday; Das, Vinita; Awasthi, Shally (Indian Journal of Community Health, 2012)
Background: Antenatal care (ANC) is a pivotal factor for the safe motherhood, but its utilization varies across the immensely varied Indian society, which by and large reside in urban slums and rural areas. Objective: To assess the sociodemographic determinants, extent of ANC utilization and impact of National Rural Health Mission (NRHM) on ANC utilization in urban slum and rural areas of Lucknow. Materials and Methods: A cross sectional study was conducted at Bal Mahila Chikitsalaya, Aliganj, an urban area of Lucknow and Primary Health Centre, Bakshi Ka Talaab, a rural area of Lucknow between October 2008 to April 2009. A total of 682 recently delivered women (within 42 days of delivery) who came to these health facilities for their child’s vaccination were interviewed, by a preformed and pretested schedule. Results: Sociodemographic determinants of ANC were age, parity, religion and socioeconomic status (SES) of the women. Hindu women, those of lower age and parity and higher socioeconomic class formed the maximum utilization groups. Education and residential area (urban or rural) of the women was found to have no influence on their utilization level of ANC services. More than half of the women had first ANC visit within first four months of pregnancy and had three ANC visits. Majority of both urban and rural women had received tetanus toxoid vaccination and Iron Folic Acid supplementation. Nearly 80% urban and 50% rural women had their weight measured, blood pressure recorded and blood and urine tests done. Conclusion: Efforts are required for covering each and every antenatal mother for complete ANC package.